2021
DOI: 10.5603/gp.a2021.0051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the consistency ratios of cervical smear, cervical biopsy and conization results

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…The scale of histopathological verification is yet another proof of the high sensitivity of the cytologic findings. Higher correlation rates between cyto-diagnostics and histopathology correspond to a more reliable quality of the diagnostics [11]. In this study, special care was taken when analyzing the cytological findings of HSIL and carcinoma, and the correlation scale was the highest for those cases -100% for carcinoma and 76% (37/49) for HSIL CIN 2 (+).…”
Section: Discussionmentioning
confidence: 88%
“…The scale of histopathological verification is yet another proof of the high sensitivity of the cytologic findings. Higher correlation rates between cyto-diagnostics and histopathology correspond to a more reliable quality of the diagnostics [11]. In this study, special care was taken when analyzing the cytological findings of HSIL and carcinoma, and the correlation scale was the highest for those cases -100% for carcinoma and 76% (37/49) for HSIL CIN 2 (+).…”
Section: Discussionmentioning
confidence: 88%
“…The full text of 26 studies was assessed. Thirteen studies [12][13][14][15][16][17][18][19][20][21][22][23][24] were excluded because they did not report the recurrence rate or did not report it for the specific group of interest, and one study 25 was excluded because it included patients without biopsy-confirmed CIN2-3 lesions. Thus, 12 studies with 1,036 patients were included in the systematic review (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Otro estudio determinó que existe una discrepancia importante entre los resultados de la citología comparada con la histología de la biopsia cervical para determinar lesiones escamosas intraepiteliales de alto grado del 50% 21 . Un amplio y reciente estudio realizado en Latino América reporto que la sensibilidad para diagnosticar NIC 3+ de la citología fue de 48,5%, evidenciándose además variaciones de la sensibilidad de la citología de acuerdo al centro de estudio del cual provenían entre un 32,1% a 87,5% 22 .…”
Section: Discussionunclassified